x = 1 9 + 1 9 + 1 9 + 1 9 + 1 9 + x 9 1 9 1 9 1 9 1 9 1
Find A 2 , where A is the sum of the absolute values of all roots of the equation above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
used same logic.
In your quadratic equation sum can directly be found which is -b/a=19^0.5=A. Hence A^2=19 ans. Pls recheck.....
Log in to reply
The problem asks for the sum of absolute values of the roots, not simply the sum of roots.
Log in to reply
Recall that the absolute value of any complex number a + i b is a 2 + b 2 . And all real numbers are complex numbers.
Log in to reply
@Manish Mayank – So? What if b is zero? The expression reduces to |a|. And the expression does have real roots.
Yes please check your answer ..... Even I think the answer should be 19...
If this were not a maths site, i'd be concerned! (Regarding the name of the problem... )
I forgot adding the absolute value of roots
Highly overrated problem! Still,
x = 1 9 + 9 1 / x . Solving this quadratic yields,
x 1 = 1 9 + 3 8 3 / 2 And x 2 = 1 9 − 3 8 3 / 2
Hence ( ∣ x 1 ∣ + ∣ x 2 ∣ ) 2 = 3 8 3
We can convert problem in infinite loop problem by repeated substitution of x and then use infinite loop method to solve it
Problem Loading...
Note Loading...
Set Loading...
Let f ( x ) = 1 9 + x 9 1 . Then x = f ( f ( f ( f ( f ( x ) ) ) ) ) , from which we realize that f ( x ) = x . This is because if we expand the entire expression, we will get a fraction of the form c x + d a x + b on the right hand side, which makes the equation simplify to a quadratic. As this quadratic will have two roots, they must be the same roots as the quadratic f ( x ) = x . The given finite expansion can then be easily seen to reduce to the quadratic equation x 2 − 1 9 x − 9 1 = 0 . The solutions are x ± = 2 1 9 ± 3 8 3 . Therefore, A = ∣ x + ∣ + ∣ x − ∣ = 3 8 3 . We conclude that A 2 = 3 8 3 .